Dystrophy of the Sense of Incomprehension and its Consequences - O. A. Donskikh (Высшее образование в России)
The problem under investigation directly relates to a radically new social situation – the possibility to immediately get any information, which has drastically changed the process of education. This situation has superimposed some previous tendencies, particularly the simplification of tasks and diminishing of challenging conditions of education from the very beginning, which leads to diminishing the joy of learning and efforts to overcome difficulties. The trend towards early specialization plays the same role, because in reality it usually only leads to the exclusion of some subjects. Special attention is given to the distinction between information and knowledge. The crucial difference is between “obtaining knowledge” and “being informed”. Generally speaking, in the first case, a person has to construct an integrated picture of the fragment of reality with different links and relationships between parts of this picture. In the second case, the bits of information are added to something already known without endeavor to continue any further work to understand the subject on a deeper level. In relation to the process of comprehension, this means that in the first case we move from the surface level to the deeper one, while in the second case we are left on the surface level. Short-term memory is used instead of long-term memory. Also, the changed ratio between oral and written communication is analyzed. Due to the habitual practice of communication using electronic devices, the predominantly oral verbal dialogues are replaced with written ones. Therefore, the connection between actors of communication becomes 1) stretched and more muddled due to the mediation of written text, and 2) much narrower, because it lacks additional hints usual for oral communication. The integral result of such education expresses itself in a certain quality of personality that can be described as “the acquired dystrophy of the sense of incomprehension.” It has extremely significant negative consequences related to the formation of a free personality, for social life, and for genuine professional education.